2022
DOI: 10.3389/fnut.2022.858089
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Availability and Sociodemographic Associated Factors in a Brazilian Municipality

Abstract: The availability of ultra-processed foods in a municipality tends to be related to different types of food retailers and their location in the territory, besides social, economic, and demographic factors. The aim of this study was to evaluate the availability of ultra-processed foods according to different types of food retailers and sociodemographic factors. This is a cross-sectional observational study carried out with audit data from food retailers in the municipality of Jundiaí, SP. Using a validated instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…This situation is associated with impoverished diet quality [ 19 ], overnutrition [ 20 ] and increased all-cause mortality [ 21 ], with people with lower educational and socio-economic status being the most affected [ 9 , 10 ]. Understanding that the gaps in nutritional education and the food industry’s marketing deepen this problem [ 8 ], the use of food classification systems by health organizations would help the population to make better choices about what they consume. Along these lines, in the last decade, different classification systems have emerged, and from this, proposals for consumption recommendations, with inconsistencies between them [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is associated with impoverished diet quality [ 19 ], overnutrition [ 20 ] and increased all-cause mortality [ 21 ], with people with lower educational and socio-economic status being the most affected [ 9 , 10 ]. Understanding that the gaps in nutritional education and the food industry’s marketing deepen this problem [ 8 ], the use of food classification systems by health organizations would help the population to make better choices about what they consume. Along these lines, in the last decade, different classification systems have emerged, and from this, proposals for consumption recommendations, with inconsistencies between them [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These products are characterized by a high calorie content and poor nutritional value, established by their high levels of sugar, fat and sodium, as well as being deficient in essential micronutrients [ 7 ]. Moreover, in different parts of the world, they constitute a cheaper and more accessible dietary alternative for the population [ 8 ], creating a complex dilemma for economically vulnerable communities, since, due to their limited food education, they often opt for the high consumption of this group of foods [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the above, it is worrying how much UPF is available for commercialization in Quilombola communities. Regarding this issue, Serafim et al [59], in a study carried out in a city in Brazil, found a higher score of availability of UPF in regions with lower income, a higher percentage of non-white people, and a higher number of residents per household. This finding demonstrates that vulnerable populations, such as the Quilombolas, are having their food consumption influenced by the industry and trade of unhealthy food products, especially UPF, which represents a risk to the health of the population due to its relationship with the development of NCDs [60].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, consumption of ultra‐processed foods that are low in nutritional value, or possess negative characteristics (such as alterations to the food matrix that may make it easier to eat more and faster, having a high energy density, or being less satiating 4 ), are being linked to socioeconomic background and ethnicity 10 . For example, in Brazil, differences in access to markets selling fresh food, healthy food being prohibitively expensive, and the existence of food deserts all play a role in creating inequality in access to un‐processed foods; in addition convenience makes ultra‐processed foods more accessible for many 10 . It is not enough to simply advise against the consumption of ultra‐processed foods, which for many may be the only viable option.…”
Section: The Complicated Landscape Of Ultra‐processed Foodmentioning
confidence: 99%